Odpowiedź :
Odpowiedź i szczegółowe wyjaśnienie:
[tex]log_2(3-log100)=log_2(3-log10^2)=log_2(3-2log10)=log_2(3-2\cdot 1)=\\=log_2(3-2)=log_21=log_22^0=0log_22=0\cdot 1=0\\\\log_66^5+log_{0.1}100=5log_66+log_{0,1}(0,1)^{-2}=5+(-2)=5-3=3\\\\log_20,25=log_2\frac14=log_24^{-1}=log_2(2^2)^{-1}=log_22^{-2}=-2log_22=-2\\\\log_{\sqrt2}4=log_{\sqrt2}(\sqrt2)^4=4log_{\sqrt2}\sqrt2=4\cdot1=4\\\\log_264=log_22^6=6log_22=6\\\\log{\frac13}3=log_{\frac13}(\frac13)^{-1}=-1log_{\frac13}\frac13=-1\cdot1=-1\\\\log_5625=log_55^4=4log_55=4\cdot1=4\\\\[/tex]
[tex]log_749=log_77^2=2log_77=2[/tex]
Wykorzystano podstawowe własności logarytmowania:
[tex]log_aa=1\\log_a1=0\\\\log_ab^n=n\cdot log_ab[/tex]